Investigation of the Effect of using Natural Gas as a Fuel on the S.I.E Behavior in Passenger Cars in Egypt - Gamal M Hennes, Ayman A Shawky, Ibrahim M Omran (International Journal of Advanced Science and Technology, 2020)
The major challenge in Egypt is to direct the passenger vehicles owners to using another fuel instead of petrol in their vehicles by adding CNG kit. This generates some major problems as a result.Different incentive scenarios are also carefully studied in order to attract more customers and change their perception about the advantage and safety of using CNG as an alternative fuel. In Egypt many diagnoses and side effect has been faced in petrol engineswhich areprovided with CNG kitsuch as misfire, Valve seats recession, backfire and low service life of engine. The objective of this study is toinvestigate the effect of using natural gas as a fuel in the internal combustion engine on the engine behavior in passenger cars.Egyptian customers using CNG kit complainfrom their vehicles performance.Many technical problems have been faced in vehicles which are designed to operate by the petrol in most efficient technique. The main approach for solving these problems was to decrease the negative side effects on theengine when operating on CNG Mode. This was achieved by investigation of the temperature around the exhaust valves in CNG mode, Measurement of the Hardness of exhaust valves,Modifying angle of exhaust valvestends to increase wear resistance and service life of exhaust valves and valve seats by 35% due to an increase in seat resting zone and that led to increasing engine service life.